SAT0408 Both clinical and ultrasonographic evaluation of synovitis are relevant to predict subsequent radiological deterioration in rheumatoid arthritis. (23rd January 2014) - Dougados, M.; Devauchelle-Pensec, V.; Ferlet, J.-F.; Jousse-Joulin, S.; D'Agostino, M.-A.; Backhaus, M.; Bentin, J.; Chalès, G.; Chary-Valckenaere, I.; Conaghan, P.; Etchepare, F.; Gaudin, P.; et al.
Abstract : Background: Presence of synovitis has been demonstrated to be predictive of subsequent structural deterioration in rheumatoid arthritis (RA). In comparison to physical examination, ultrasonography (US) seems to be more accurate (sensitive) for the detection of synovitis. Objectives: To compare the predictive validity of synovitis with regard to the joint examination modality ( e.g. clinical versus US). Methods: Patients: Definite active RA. Study design: Prospective, 2 year follow-up. Data collected: For each patient, 32 joints were evaluated (2 wrists, 10 MCP, 10 PIP, 10 MTP). Information of synovitis was collected at baseline at physical and US (Grey Scale (GS) and US Power Doppler (PD)) examinations by 2 distinct physicians. X-rays of the 32 joints performed at baseline and year 2 were evaluated (presence of both erosion and joint space narrowing) by another distinct physician. Analysis: Measures of association (odds ratio [OR]) and 95% confidence intervals [CI] were tested between the structural deterioration defined by an occurrence or a worsening of joint space narrowing or bone erosion and the presence of synovitis defined by clinical, US-GS or US-PD at baseline. These measures of association were tested using generalized estimating equation (GEE) analysis adjusting for within patient correlation and also other factors ( e.g. age, gender, disease duration, baseline DAS28 and baseline joint structural damage). Results: Of the 77 recruited patients, 59 had a complete data set. After 2 years of follow-up, a structural deterioration was observed in 9% of the 1888 evaluated joints The increased probability to observe a structural progression in presence of synovitis was confirmed for the different joint examination modalities: OR =2.08 [1.39-3.11] p <0.01 versus 1.64 [1.08-2.47] p =0.019 versus 1.80 [1.20-2.71] p =0.005 for the clinical versus US-GS versus US-PD evaluation respectively. In the 1101 joints with normal baseline clinical evaluation, an increased probability to observe a structural progression in presence of US synovitis was also observed (OR =2.22 [1.20-4.08] p< 0.011 and 3.93 [1.93-7.99] p =0.001 for the US-GS and US-PD evaluation respectively). Inversely, in the 938 joints with normal baseline US evaluation (both GS and PD), an increased probability to observe a structural progression in presence of baseline clinical synovitis was still observed (OR =2.95 [1.50-5.81] p =0.002). Conclusions: This study confirms the validity of synovitis to predict subsequent structural deterioration whatever the joint examination modality but suggests also that BOTH clinical AND ultrasonographic examinations are relevant to optimally evaluate the risk of subsequent structural deterioration Disclosure of Interest: M. Dougados Grant/Research support from: abbott, V. Devauchelle-Pensec: None Declared, J.-F. Ferlet: None Declared, S. Jousse-Joulin: None Declared, M.-A. d'Agostino: None Declared, M. Backhaus: None Declared, J. Bentin: None Declared, G. Chalès: None Declared, I. Chary-Valckenaere: None Declared, P. Conaghan: None Declared, F. Etchepare: None Declared, P. Gaudin: None Declared, W. Grassi: None Declared, D. van der Heijde: None Declared, X. Mariette: None Declared, E. Naredo: None Declared, M. Szkudlarek: None Declared, R. Wakefield: None Declared, A. Saraux: None Declared